Twenty years of experience with less radical fertility-sparing surgery in early-stage cervical cancer: Oncological outcomes - Hruda, Martin; Robova, Helena; Rob, Lukas; Halaska, Michael J; Drozenova, Jana; Pichlik, Tomas; Malikova, Hana (Gynecologic oncology, 2021)
INTRODUCTION: The standard procedure in cervical cancer is radical hysterectomy (RH) and pelvic lymphadenectomy (PLND). Because of the increasing age of women at childbirth, fertility becomes a major challenge. We present 20 years of experience with two-step less radical fertility-sparing surgery in women with IA1, LVSI positive, IA2 and IB1 (<2 cm, infiltration less than half of stromal invasions. MATERIALS AND METHOD: Preoperative workout consisted of histopathological diagnosis and magnetic resonance imaging along with ultrasonographic volumetry. We then performed laparoscopic sentinel lymph node mapping (SLNM) with frozen section (FS) followed by PLND and "selective parametrectomy" (removal of afferent lymphatic channels from the paracervix) in case of a negative result. If verified by definitive histopathology, patients were treated by simple trachelectomy (IB1) or large cone (IA1/IA2) biopsy 1 week after primary surgery. RESULTS: From 1999 to 2018, 91 women were enrolled in the study (median age 29.1 years, range 21-40). Of these 91 women, 51 (56.0%) were nulliparous. The detection rate of SLNs was 100% per patient and the specific side detection rate 96.7%. Positive lymph nodes were diagnosed in nine cases (9.8%). These women then underwent RH. Fertility was spared in 80 women but 4 recurred locally (5.0%). The mortality rate was 0.0%. The median follow-up was 149 months. CONCLUSION: Less radical fertility-sparing surgery with SLNM is safe in cervical cancers <2 cm at the largest diameter and infiltrating less than half of the cervical stroma. The recurrence rate is acceptable with no mortality. Morbidity with this procedure is low. Extended and accurate follow-up is necessary and human papillomavirus - high risk (HPV-HR tests seem to be useful in such follow-up assessment.
Keywords: Humans; zachování plodnosti; Fertility Preservation; Cervical cancer; Less radical fertility-sparing surgery; Female; trachelektomie; dospělí; mladý dospělý; nádory děložního čípku; Oncological outcomes; lidé; Lymph Node Excision; Adult; Trachelectomy; Sentinel lymph node mapping; staging nádorů; ženské pohlaví; hysterektomie; Uterine Cervical Neoplasms; Young Adult; lymfadenektomie; Hysterectomy; Neoplasm Staging; lokální recidiva nádoru; prospektivní studie; Neoplasm Recurrence, Local; Prospective Studies